Airflow in stop-vowel sequences of German - Hamann, Silke; Velkov, Hristo (ZAS Papers in Linguistics, 2005)
This study reports on the results of an airflow experiment that measured the duration of airflow and the amount of air from release of a stop to the beginning of a following vowel in stop vowel-sequences of German. The sequences involved coronal, labial and velar voiced and voiceless stops followed by the vocoids /j, i:, ı, ɛ, ʊ, a/. The experiment tested the influence of the three factors voicing of stop, place of stop articulation, and the following vocoid context on the duration and amount of air as possible explanation for assibilation processes. The results show that the voiceless stops are related to a longer duration and more air in the release phase than voiced ones. For the influence of the vocoids, a significant difference could be established between /j/ and all other vocoids for the duration of the release phase. This difference could not be found for the amount of air over this duration. The place of articulation had only restricted influence. Velars resulted in significantly longer duration of the release phase compared to non-velars. A significant difference in amount of air between the places of articulation could not be found.